A handy way to estimate lean body mass and fuel load from wing length: a quantitative approach using magnetic resonance data. Issue 1 (2nd January 2019) - Kelsey, Natalie A.; Schmaljohann, Heiko; Bairlein, Franz
ABSTRACT: Knowledge about fuel load of migratory birds is important for understanding their migration in general, as it affects for example departure decisions from stopovers and the distance to fly. In field ornithology, indirect estimates of fuel load through biometric approaches and fat scoring are widely used because direct and thus more accurate estimates of fat and lean mass are hardly applicable in the field or require sacrificing of the bird. In this study, we used quantitative magnetic resonance technology to directly measure fat and lean mass of 5390 individuals of 21 Palearctic migratory songbird species captured on Helgoland during spring and autumn migration. Based on these data, a general multi-species model demonstrated that the bird's lean body mass is positively related to its wing length. In relation to this species-unspecific dependency, species-specific relationships were developed. For all species, we provide the equations to estimate individual fuel loads solely based on the bird's wing length and current body mass. Our results are in line with former approaches, but our approach yields slightly more precise estimates and applies to more species, presenting a handy and easy tool for field ornithologists to evaluate the amount of fuel carried by their study bird.